Ritus Sedekah Laut sebagai Mekanisme Sosial Masyarakat Nelayan Urban di Muarareja Kota Tegal - Amanatin, Elsa Lutmilarita; Sekarningrum, Bintarsih; Supangkat, Budiawati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The tradition of Sedekah Laut in Muarareja, Tegal City, is a crucial aspect of the social and cultural life of urban fishing communities. This tradition not only holds religious significance but also plays a vital role in maintaining collective identity and social cohesion amidst rapid social and economic changes. This study aims to elucidate how the ritual of Sedekah Laut in Muarareja functions as a social mechanism among urban fishing communities. Employing a qualitative approach, the research utilized semi-structured interviews with 7 urban fishermen and 3 community members from Muarareja, direct observations, and documentary analysis for data collection. Findings indicate that Sedekah Laut serves not only as a religious ceremony but also as a manifestation of strong social solidarity and sustainable social networks within the fishing community. The study concludes that firstly, Sedekah Laut plays a crucial role in preserving the cultural continuity and community identity of fishermen in Muarareja; secondly, it strengthens social relations among individuals and groups within the community; thirdly, the ritual demonstrates its adaptability and relevance amidst the dynamic social and economic changes along the coastal region. This research provides a foundation for understanding how local traditions can support social and cultural sustainability in continuously transforming coastal communities. The study recommends further interdisciplinary research to deepen understanding of the impacts and significance of this tradition in an evolving global context.